2003
DOI: 10.14430/arctic618
|View full text |Cite
|
Sign up to set email alerts
|

Trends in Forage Fish Populations in Northern Hudson Bay since 1981, as Determined from the Diet of Nestling Thick-billed Murres, <i>Uria lomvia</i>

Abstract: ABSTRACT. Trends in the composition of nestling thick-billed murre diets were analyzed for the period 1980 -2002 on the basis of observations of food delivered to nestlings at two breeding colonies in northern Hudson Bay. The incidence of arctic cod, sculpins, and benthic Zoarcidae decreased and the incidence of capelin and sandlance increased over the period considered. Arctic cod fell from a mean of 43% of deliveries in the mid-1980s to 15% in the late 1990s; benthic species (zoarcids and sculpins) fell from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
133
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 151 publications
(139 citation statements)
references
References 32 publications
6
133
0
Order By: Relevance
“…The NHB food web has been changing in the last 30 years as a result of climatic change in the region, which has resulted in an increase in capelin and sandlance (Ammodytes sp.) and a decrease in Arctic cod and some benthic species (Gaston et al 2003). It is possible that, if necessary, narwhals may be able to switch primary prey and monopolize on the increase in capelin abundance, which may mitigate the negative impacts of reduced cod and benthic species.…”
Section: Discussionmentioning
confidence: 99%
“…The NHB food web has been changing in the last 30 years as a result of climatic change in the region, which has resulted in an increase in capelin and sandlance (Ammodytes sp.) and a decrease in Arctic cod and some benthic species (Gaston et al 2003). It is possible that, if necessary, narwhals may be able to switch primary prey and monopolize on the increase in capelin abundance, which may mitigate the negative impacts of reduced cod and benthic species.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the rapidity of climate change-induced shifts in habitats and trophic food webs could affect contaminant toxicity by altering exposure pathways and increasing susceptibility of some populations, especially those already under stress (AMAP, 2004;Breivik et al, 2004;Brook and Richardson, 2002;Gaston et al, 2003;Gilbertson et al, 2003;Macdonald et al, 2005;Olafsdottir et al,1998;Sagerup et al, 2000). A limitation of studies investigating the interactive toxicity of climate change and contaminant exposures is that observed biological effects may prove to have a non-linear relationship to the stressors.…”
Section: Effects Of Climate Change On Contaminant Toxicity To Wildlifementioning
confidence: 99%
“…For example, Arctic cod (Boreogadus saida) are a primary, high fat forage fish for many Arctic species, and loss of critical sea ice habitat may adversely affect Arctic cod populations and those animals that rely on them for food. Gaston et al (2003) analyzed the diets of thick-billed murres from 1981-2002, and observed a decrease in consumption of Arctic cod. This shift in diet increased the fat burned to the fat energy gained.…”
Section: Altered Ecosystemsmentioning
confidence: 99%
“…Marine bird population monitoring in arctic Canada has been key in developing or influencing policies to understand the effects of climate change on these species (Gaston et al 2005a,b), as well as for understanding changes in food webs that might affect reproduction (Gaston et al 2003). For murres, an internationally-harvested species, these monitoring data also contribute to setting harvest limits and understanding the effects of harvest quotas on sustainable management .…”
Section: How Do Long-term Time Series Data Help In Management?mentioning
confidence: 99%
“…For example, in the case of acid rain in eastern North America, the negative influence of El Niño events on ecosystem recovery was only discerned through interpretation of anomalies in the long-term water chemistry monitoring of lakes and streams (e.g., Dillon et al 1997). Similarly, changes in fish communities in northern Hudson Bay were only recognized by long-term monitoring of seabird diets at Coats Island (Gaston et al 2003). Hence, long-term data are also important in ecology because they generate questioning and reformulating of views of the natural world, challenge current predictions about ecological trends and phenomena, and provide the ability to assess the effectiveness of resource management decisions.…”
Section: Introductionmentioning
confidence: 99%